Sull’utilità della Storia delle donne per rileggere il protagonismo di Adelaide Ristori - Mariani, Laura (Drammaturgia, 2023)
I propose to rethink Adelaide Ristori in a hitherto unconsidered context: a History of the actor that places the category of gender at the centre, not as an add-on but as a problematic function, in order to investigate the specificity – if it exists and how it is configured – of the experience and acting of theatre actresses, starting with the body. Ristori plays a central role in this perspective, in particular in relation to the following aspects: work on the character, definition of repertoire, construction of celebrity. On the one hand, the choice and performance of exceptional female characters must be investigated, since they strike the audience on an emotional level and are fixed in the memory by emblematic images, as well as they propose non-masculine models of strength and authority to female spectators. And, on the other hand, the intelligence, originality, and tenacity with which Ristori represents herself should be analysed, such as to configure an early divine construction, before Sarah Bernhardt and Eleonora Duse and the cinema itself. A construction that cannot take advantage of the possibility of films to reach large masses, but which cleverly links the public and private spheres, almost evoking the horizontal action of the present-day media.